Venom - Singer, Marilyn (Plain City, OH Darby Creek Publishing, 2007)
Learn about venom and the animals that produce it and use it to survive, including spiders, insects, snakes and other reptiles, frogs and toads, fish, and ocean invertebrates.
Elementary
Keywords: Poisonous animals; Venom